Enhancement of elastic properties and surface plasmon resonance with the addition of boron oxide to the ZnO−SiO2 glass system - Al-Nidawi, A.J.A.; Matori, K.A.; Zaid, M.H.M.; Liew, J.Y.C.; Khushaini, M.A.A.; Zain, A.R.M.; Mutage, W.R.M.; Abuallan, M.A.M.; Efa, A.M.E. (Elsevier, 2023)
Glass substrates, with their ultrasonic and enhanced Raman signals, are ever-demanding for medical applications. This paper reports the effect of boron addition to the enhancement of the elastic properties and Raman shifting in the Surface Plasmon Resonance results for the zinc borosilicate glass substrate that can be used for optical biosensor applications. Such glasses were prepared by melt“the quenching method and characterized using a densimeter, X-ray diffraction measurement, Fourier transforms infrared spectroscopy, ultrasonic, and surface plasmon resonance spectroscopy. Results from the current study demonstrated how the composition of the glass influences the physical and elastic moduli of the boron-doped zinc silicate series. The physical characteristics of the zinc silicate glasses were predicted to alter significantly after adding boron as a modifier. The glass density decreased from 3392 to 2983 kg/m3 as the percentage of boron increased from 0.10 to 0.20 wt., then increased to 3191 kg/m3 at 0.30 wt.. The X-ray diffraction and Fourier transforms infrared spectroscopy techniques verified the amorphous glass phase. The ultrasonic method determined the glass's ultrasonic longitudinal and shear velocity at a 5 MHz resounding recurrence at room temperature to study elastic moduli. When boron content is added, the longitudinal, Young, shear, and bulk moduli exhibit a decreasing and increasing trend. As the boron content increases and behaves as a modifier, the number of non-bridging oxygen will increase, which will cause the glass network to expand. In addition, the increase in Eopt occurs from 3.4883 to 3.4331 because the sample has a higher number of non-bridging oxygen. The shift for Otto configuration of the SPR results occurs with the increase of boron concentration. The fabricated glass can potentially be used to construct an integrated silicon-based glass substrate for an optical sensor.